2022
DOI: 10.1111/jace.18609
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of anisotropic bonded magnets prepared by additive manufacturing

Abstract: In this research, anisotropic NdFeB + SmFeN hybrid and NdFeB bonded magnets are additively printed in a polyphenylene sulfide (PPS) polymer binder. Printed NdFeB + SmFeN PPS bonded magnets displayed excellent magnetic properties (Br [remanence] = 6.9 kG [0.69 T], Hcj [coercivity] = 8.3 kOe [660 kA/m], and BHmax [energy product] = 9.9 MGOe [79 kJ/m3]) with superior corrosion resistance and thermal stability. The anisotropic NdFeB bonded magnet shows a high coercivity of 14.6 kOe (1162 kA/m) with a BHmax of 8.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The effect is illustrated in Figure 3a-c. both NdFeB and SmFeN because the magnetic flux decreased by much less than 1% of the value measured for uncoated magnets [12]. after dipping in the acid solution for 24 h at room temperature, the uncovered NdFeB magnet partially corroded, so the saturated magnetization dropped to 98 emu, while the covered magnet remained intact; (c) after dipping in the acid solution for 100 h at 80 °C, the uncovered NdFeB magnet corroded significantly, so the saturated magnetization dropped to 32 emu, while the covered magnet remained intact.…”
Section: Adhesive Coatingsmentioning
confidence: 74%
See 2 more Smart Citations
“…The effect is illustrated in Figure 3a-c. both NdFeB and SmFeN because the magnetic flux decreased by much less than 1% of the value measured for uncoated magnets [12]. after dipping in the acid solution for 24 h at room temperature, the uncovered NdFeB magnet partially corroded, so the saturated magnetization dropped to 98 emu, while the covered magnet remained intact; (c) after dipping in the acid solution for 100 h at 80 °C, the uncovered NdFeB magnet corroded significantly, so the saturated magnetization dropped to 32 emu, while the covered magnet remained intact.…”
Section: Adhesive Coatingsmentioning
confidence: 74%
“…The unfavorable results reported by Paranthaman et al [ 10 ] at larger temperatures between 100 and 200 °C may be explained by structural modification of this adhesive, as the highest recommended curing temperature is 93 °C. The same adhesive was also reported to be beneficial for coating hybrid magnets containing both NdFeB and SmFeN because the magnetic flux decreased by much less than 1% of the value measured for uncoated magnets [ 12 ].…”
Section: Scientific Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the BAAM process described in references, 20,22 the feedstock is obtained by first pelletizing the composite magnet powder (Sm-Fe-N and Nd-Fe-B suspended in polymer binder) and then extruded through a heated nozzle that precisely deposits each layer onto a build platform. Each layer thickness corresponds to the extruder's nozzle diameter.…”
Section: Advanced Manufacturing Of Optimized Designsmentioning
confidence: 99%
“…The optimized magnet designs presented in this work can be produced by FDM 3D printing. ORNL's BAAM 3D printer has shown that it is possible to produce these magnets 20,22 because it can handle very high magnet filler loading. However, other commercially available printers may not be equipped to process the high-volume fraction material necessary for these magnets.…”
Section: Advanced Manufacturing Of Optimized Designsmentioning
confidence: 99%